Dental caries prevention profile of children with and without sickle cell anaemia in a suburban community in Nigeria - Jacob Babatunde Afolabi; Elizabeth Obhioneh Oziegbe; Samuel Ademola Adegoke; Olufemi Adefehinti; Elijah Olufemi Oyetola; Moréniké Oluwátóyìn Foláyan (BMC Research Notes)
Abstract Background The cascade of events in children with sickle cell anaemia (SCA) may influence their caries experience. This case-control study aimed to compare the dental caries prevention profile (captured via caries experience, risk behaviours, and access patterns) of the primary and permanent dentitions of children with and without SCA in a suburban community in Nigeria. Results This is a sub-study of a larger case-control study that recruited 264 children (120 males, 144 females; mean age 9.41 ± 3.35 years). Among those with primary dentition (n = 207), 13.5% had dental caries. Children with SCA had twice the dental caries experience as those without (17.9% vs. 8.9%), though not statistically significant (p = 0.06). No significant associations were found between caries and tooth brushing, daily fluoride use, or frequency of daily consumption of refined carbohydrates. However, caries was significantly higher among children who had used dental services (50% vs. 10.9%; p < 0.001). The dmft score was significantly higher in children with SCA (p = 0.04) and girls (p = 0.02). In permanent teeth, children with SCA with fair hygiene had higher DMFT scores (p = 0.03). Clinical trial number Not applicable.